Digital Childhood: Exploring the Influence of Smartphones on Children's Social Competence and Emotional Regulation - Sirjon; Jumriani (Universitas Pendidikan Ganesha, 2026)
This study was motivated by the increasing use of smartphones among early childhood. Parents tend to let their children play without paying attention to the duration. The purpose of this study was to analyze how smartphone use affects children's social competence and emotional regulation. The subjects of the study consisted of 5 children aged 5–6 years who actively use smartphones, and their parents. The study used a qualitative case study approach with data collection techniques through observation and semi-structured interviews. Data analysis was carried out thematically through data reduction, categorization, and drawing conclusions, with data validity guaranteed through triangulation, member checking, and audit trails. The results showed that smartphone use was influenced by factors such as parental busyness and efforts to avoid conflict between siblings. The positive impacts of smartphone use for children include increasing technological knowledge, learning independence, and creativity. However, the negative impacts are more dominant, such as the emergence of aggressive behavior, individualistic attitudes, and low social and emotional abilities. In conclusion, although there are benefits, the negative impacts of smartphone use are more prominent. This research is important as a basis for developing policies and programs for early childhood education in the future.